2009
DOI: 10.1111/j.1365-2672.2009.04388.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofChlamydiaceaespecies using PCR and high resolution melt curve analysis of the 16S rRNA gene

Abstract: This technique allowed for the rapid detection and identification of the six Chlamydiaceae reference species and may be useful for identification of uncharacterized Chlamydiaceae species or for use in animal species where occurrence of the disease has not been fully investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…One, applying a family-specific PCR targeting the ribosomal genes, was able to distinguish six species by subjecting generated amplicons to high-resolution melt curve analysis (19). However, as this is a highly sensitive method allowing discrimination on the basis of a single base pair polymorphism, it also requires highly standardized conditions for preparing the master mix and clean DNA to be reproducible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One, applying a family-specific PCR targeting the ribosomal genes, was able to distinguish six species by subjecting generated amplicons to high-resolution melt curve analysis (19). However, as this is a highly sensitive method allowing discrimination on the basis of a single base pair polymorphism, it also requires highly standardized conditions for preparing the master mix and clean DNA to be reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Two real-time PCR detection systems for identification of Chlamydiaceae have been described (17,19). One, applying a family-specific PCR targeting the ribosomal genes, was able to distinguish six species by subjecting generated amplicons to high-resolution melt curve analysis (19).…”
Section: Discussionmentioning
confidence: 99%
“…HRM analysis has been used in numerous studies since the mid-2000s on a wide range of human pathogens, including those within the genera Campylobacter, Brucella, Leishmania, Bordetella, Clostridium, Mycobacterium, Mycoplasma, Chlamydophila, Cryptosporidium, and Staphylococcus, among others (445)(446)(447)(448)(449)(450)(451)(452). Recent studies have shown HRM analysis to be a powerful technique for characterizing antibiotic resistance and typing respiratory disease agents, including M. pneumoniae, C. pneumoniae, and Chlamydophila psittaci (453)(454)(455)(456)(457)(458)(459). To our knowledge, HRM analysis for intraspecies or interspecies Legionella discrimination has been included in only a few studies (460)(461)(462)(463); however, this approach seems promising for future Legionella diagnostics or typing.…”
Section: Emerging Methods and Technologiesmentioning
confidence: 99%
“…Extracted DNA was tested for the presence of Chlamydia spp. using the Chlamydia 16SG nucleotide set qPCR first described by Robertson et al (2009). The resulting melt curves from this qPCR, coupled with appropriate controls, can be used to distinguish detected Chlamydia species (Fig.…”
Section: Methodsmentioning
confidence: 99%